2015
DOI: 10.1055/s-0035-1554905
|View full text |Cite
|
Sign up to set email alerts
|

The Olfactory Strip and Its Preservation in Endoscopic Pituitary Surgery Maintains Smell and Sinonasal Function

Abstract: ).Differing outcomes on olfaction have been reported from transsphenoidal approaches. [1][2][3][4] In general, patients prefer the endoscopic approach, 5 and olfactory scores are better after the endoscopic route. 6 The nasoseptal flap, in particular, to reconstruct the skull base as part of the overall process has been implicated in smell dysfunction. However, much of the literature on the impact of the nasoseptal flap comes from extended skull base surgery. In our institution, utilizing a small modified naso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…e SNOT-22 is yet to be validated and has inherent shortcomings in its use; nevertheless, it caters as a reliable indicator of sinus-specific symptomatology in patients [18]. To date, pertinent studies have predominantly been marginal, single-institution, retrospective studies showing mixed results, although in general, they revealed a postoperative resurgence in terms of sinonasal QOL [22][23][24][25][26][27][28][29][30][31]. Ultimately, an enhanced comprehension of postoperative QOL after an endoscopic endonasal approach will aid in enriched patient counseling and disease management, besides identifying loci for focus in quality improvement initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…e SNOT-22 is yet to be validated and has inherent shortcomings in its use; nevertheless, it caters as a reliable indicator of sinus-specific symptomatology in patients [18]. To date, pertinent studies have predominantly been marginal, single-institution, retrospective studies showing mixed results, although in general, they revealed a postoperative resurgence in terms of sinonasal QOL [22][23][24][25][26][27][28][29][30][31]. Ultimately, an enhanced comprehension of postoperative QOL after an endoscopic endonasal approach will aid in enriched patient counseling and disease management, besides identifying loci for focus in quality improvement initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…Odor identification requires both peripheral sensory perception as well as central cognitive processing, and insults at any point along the pathway may compromise olfaction. Possible mechanisms associated with the olfactory neuroepithelium include age‐related atrophy; cumulative exposure to pollution, toxins, and bacteria; decrease in mucosal blood flow; chronic inflammation; impaired mucociliary function; decreased regenerative capacity; replacement with respiratory epithelium; decrease in the number and specificity of ORs; reduction in the size and number of patent foramina in the cribriform plate; impairment of immunologic and enzymatic defense mechanisms; and cellular accumulation of amyloid and tau filaments 531,536,551–553 . The OB may demonstrate atrophy, loss of neuronal elements, and decreased laminae and glomeruli with age, as well as accumulation of tau and α‐synuclein 531,536,554,555 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…These include preservation of the septal olfactory strip, avoidance of electrocautery during nasoseptal harvest, limiting the elevation of a pedicled nasoseptal mucosal flap, and preservation of the middle turbinates and upper 2/3 of the superior turbinates. 509,510,[513][514][515][516][517] For select intracranial tumors that are unilateral and amenable to access via only one nostril, a unilateral endoscopic transnasal approach with preservation of the contralateral OC and OB has been proposed to assist with smell preservation. 518 33 This rate rises to 34.5% in studies with a mean age >55 years compared with 7.5% in studies with a mean age <55 years.…”
Section: H Related To Sinonasal or Intracranial Tumormentioning
confidence: 99%
“…This may be because endoscopic transsphenoidal surgery, in order to preserve the working space for forceps and equipment, often sacri ces a portion of the middle/superior turbinate, abandons unilateral septal mucosa, and sacri ces the posterior ethmoid sinus to access the sphenoid sinus through a single nasal cavity. Damage to the nasal cavity is relatively extensive; patients often have abnormal olfactory function after surgery; it takes a long time to return to average or even permanent loss, and in severe cases, it can affect the taste (34,35). There is also a higher incidence of delayed epistaxis 36 .…”
Section: Postoperative Complicationsmentioning
confidence: 99%